Molecular cloning and phylogenetic analysis of cereal type II metacaspase cDNA from wheat - E. Piszczek; M. Dudkiewicz; M. Sobczak (Biologia Plantarum, 2011)
A new cereal type II metacaspase full-length cDNA from wheat (Triticum aestivum L.) leaves, TaeMCAII, was for the first time successfully amplified and sequenced. The full-length sequence of the TaeMCAII cDNA of 1 551 bp contains a 1 218 bp open reading frame. The deduced protein encoded by the TaeMCAII cDNA consists of 405 amino acids with a calculated molecular mass of 44 kDa and an isoelectric point of 5.29. In response to wounding or heat shock, a similar sequence of ultrastructural events including the tonoplast rupture, chromatin condensation, degradation of chloroplasts and disappearance of cytoplasm and organelles were observed using transmission electron microscopy. As the observed changes in TaeMCAII mRNA level did not occur to be statistically significant wounding-induced programmed cell death (PCD) seems to be metacaspase-independent pathway. Interestingly, in PCD caused by a heat-shock treatment, the level of TaeMCAII mRNA remained unaltered until 48 h after the stress what suggests that TaeMCAII participates in later stages of PCD triggered by heat-shock. Phylogenetic analysis enabled to classify TaeMCAII as a type II metacaspase. Finally, homology modelling of the putative three-dimensional structure of the TaeMCAII protein and a topology analysis of its probable active site were performed.